Acrylamide levels in potato crisps in Europe from 2002 to 2016. Issue 12 (2nd December 2017) - Powers, Stephen J.; Mottram, Donald S.; Curtis, Andrew; Halford, Nigel G.
ABSTRACT: European manufacturers' data on acrylamide in potato crisps from 2002 to 2016 were analysed. A previous study showed a 53% reduction in mean acrylamide levels from 763 ng g −1 in 2002 to 358 ng g −1 in 2011. Analysis of data from the longer period showed that since 2011 there has been a levelling off, with the mean level for 2016 being 412 ng g −1 (still a 46% reduction from 2002), suggesting that the most effective acrylamide reduction measures had been devised and implemented by 2011. There were similar trends in the 90 th and 95 th quantile values, with the 90 th quantile values being below 1000 ng g −1 (the European Commission's current 'Indicative Value' for acrylamide in potato crisps) since 2010. The proportion of samples with acrylamide above 2000 ng g −1 fell from 4.8% in 2002 to 0.6% in 2016. Acrylamide levels showed marked seasonal variability, being highest in the first half of the year when potatoes were being used from storage, and lowest from July to September when potatoes were being harvested. Acrylamide levels were higher in thicker types of crisp in the early years of the study, but this difference disappeared in the later years, suggesting that manufacturers had acted to reduce acrylamide formation in these products. Higher values for acrylamide were recorded in north and east Europe than in the south and west up to 2013. Levels in the north and east declined in recent years, but remained higher in the north than in the other regions. The manufacturers' data were compared with a much smaller dataset provided by the European Food Safety Authority (EFSA). Levels of acrylamide in the EFSA dataset were consistently higher than in the manufacturers' data, possibly due to uneven sampling through the year and the seasonality of acrylamide levels.